A New Extreme Detection Method for Remote Compound Extremes in Southeast China - Wang, Luqing; Zhao, Qinglin; Gao, Si; Zhang, Wei; Feng, Li (Frontiers in Earth Science, 2021)
The compound heat wave and extreme precipitation events are responsible for severe damages to the environment and human societies. Although major advances have been made in understanding the compound extremes (e.g., drought and heat wave), little is known about two types of extremes synchronized/connected in different regions. Here we identify a new type of compound extreme termed as “remote compound extreme” with the aid of a new extreme value detection method that combines isolated forest and quantile statistics. The new compound extremes are reflected by a statistically significant correlation (i.e., 0.52) between heat wave in the Pearl River Delta and extreme precipitation in the middle and lower reaches of the Yangtze River Delta. The remote compound extreme is tied to the western Pacific subtropical high that modulates surface temperature in the Pearl River Delta and extreme precipitation in the middle and lower reaches of the Yangtze River Delta.